Teaching reaction kinetics through isomerization cases with the basis of density-functional calculations - Rusydi, Febdian; Madinah, Roichatul; Ira Puspitasari; Lee, Mark Wun Fui; Ahmad, Azizan; Rusydi, Andrivo (John Wiley & Sons, 2021)
The fundamental mechanism of biochemistry lies on the reaction kinetics, which is determined by the reaction pathways. Interestingly, the reaction pathway is a challenging concept for undergraduate students. Experimentally, it is difficult to observe, and theoretically, it requires some degree of physics knowledge, namely statistical and quantum mechanics. However, students can utilize computational methods to study the reaction kinetics without paying too much attention but not wholly neglecting the comprehension of physics. We hereby provided an approach to study the reaction kinetics based on density-functional calculations. We particularized the study of the isomerization case involving five molecules at three different temperatures and emphasized the importance of the transition state in the study of reaction kinetics. The results we presented were in good agreement with the experiments and provided useful insights to assist students in the application of their knowledge into their research.